2017
DOI: 10.7150/oncm.17020
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 Inhibitors, a Potential Synergistic Effect with Antineoplastic Drugs in Lung Cancer

Abstract: Background: Lung cancer represents the leading cause of cancer-related deaths worldwide and novel therapeutic approaches targeting crucial pathways are urgently needed to improve its treatment. Inflammation plays a critical role in multistage tumor development and increased evidence has supported the involvement of cyclooxygenase-2 expression in carcinogenesis. We investigated the potential use of COX-2 inhibitors in cancer proliferation and apoptosis. Methods: Celecoxib, rofecoxib, etoricoxib, meloxicam, ibuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…It was shown that increased expression of COX-2 in non-small cell lung cancer (NSCLC) plays a significant role in lung cancer development through its effect on angiogenesis and immune response suppression in tumour cells (40,41). The literature data show that carcinogenesis can be decelerated by the use of COX-2 inhibitors not only as single agents, but also in combined therapy (40)(41)(42). Therefore, an increased level of ZYX in response to the application of COX-2 inhibitor suggests the ability of ZYX to inhibit oncogenesis.…”
Section: The Role Of Zyxin In Carcinogenesismentioning
confidence: 99%
“…It was shown that increased expression of COX-2 in non-small cell lung cancer (NSCLC) plays a significant role in lung cancer development through its effect on angiogenesis and immune response suppression in tumour cells (40,41). The literature data show that carcinogenesis can be decelerated by the use of COX-2 inhibitors not only as single agents, but also in combined therapy (40)(41)(42). Therefore, an increased level of ZYX in response to the application of COX-2 inhibitor suggests the ability of ZYX to inhibit oncogenesis.…”
Section: The Role Of Zyxin In Carcinogenesismentioning
confidence: 99%
“…Another study suggested a limited dose-dependent effect on cell proliferation in human colorectal carcinoma cell lines [91]. In a study, rofecoxib (40 µM), in combination with docetaxel, was found to be more cytotoxic to lung cancer cell lines than docetaxel alone [92]. Rofecoxib was also reported to prevent DNA damage induced by ultraviolet B radiation and copper ions.…”
Section: Rofecoxib (Vioxx)mentioning
confidence: 99%